2019
DOI: 10.1128/aem.01281-19
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the Subtilase Cytotoxin Gene subAB 1 in Shiga Toxin-Producing Escherichia coli Is Dependent on hfq and hns

Abstract: Certain foodborne Shiga toxin-producing Escherichia coli (STEC) strains carry genes encoding the subtilase cytotoxin (SubAB). Although the mode of action of SubAB is under intensive investigation, information about the regulation of subAB gene expression is currently not available. In this study, we investigated the regulation of the chromosomal subAB1 gene in laboratory E. coli strain DH5α and STEC O113:H21 strain TS18/08 using a luciferase reporter gene assay. Special emphasis was given to the role of the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The authors assumed that the LEE-negative STEC strains used in the study might probably be the reason for the discrepancy to the study of Li et al, who examined the influence of H-NS in a LEE-positive EHEC O157:H7 strain [31]. This assumption is further supported by the results obtained in our group, in which a deletion of hns in the eae -negative STEC O113:H21 strain TS18/08 (first described in [32]) was constructed for the purpose of another research project concerning subtilase cytotoxin expression [33]. The hns deletion mutant showed a hyper-hemolytic phenotype on blood agar plates, whereas the complementation of the mutant with a recombinant hns gene on a medium-copy plasmid restored the characteristic wild-type turbid lysis zones.…”
Section: Regulation Of Ehec-hlya Expressionsupporting
confidence: 57%
“…The authors assumed that the LEE-negative STEC strains used in the study might probably be the reason for the discrepancy to the study of Li et al, who examined the influence of H-NS in a LEE-positive EHEC O157:H7 strain [31]. This assumption is further supported by the results obtained in our group, in which a deletion of hns in the eae -negative STEC O113:H21 strain TS18/08 (first described in [32]) was constructed for the purpose of another research project concerning subtilase cytotoxin expression [33]. The hns deletion mutant showed a hyper-hemolytic phenotype on blood agar plates, whereas the complementation of the mutant with a recombinant hns gene on a medium-copy plasmid restored the characteristic wild-type turbid lysis zones.…”
Section: Regulation Of Ehec-hlya Expressionsupporting
confidence: 57%
“…The ligation was conducted at 22 °C for one hour. Subsequently, ligation batches were transformed to chemically competent E. coli DH5α as described previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…To verify constructed plasmids, they were sequenced by Sanger sequencing using primers pET22-seq-for and pET22-seq-rev (see Table 2 ) as described earlier [ 51 ]. After confirmation of the correct insertion of the stxA2a and stxB2a genes in the pET22b(+) expression vector, plasmids were transformed to chemically competent E. coli C41 (DE3) or competent E. coli C43 (DE3) cells, respectively, as described earlier [ 25 ]. The expression plasmids for stxA2a and stxB2a were designated pKR09 and pKR10, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the regulation of subAB gene expression is still unknown, the latest study showed that transcription of subAB 1 is regulated by hfq and hns in the STEC O113:H21 strain. 17 Generally, Shiga toxin (Stx) 2 expression in LEE-positive STEC O157:H7 is enhanced by treatment with H 2 O 2 or antibiotics. 18 However, our recent findings suggest that both Stx2 and SubAB expressions in LEE-negative STEC O113:H21 are not promoted by antibiotics, mitomycin C, or H 2 O 2 (unpublished data).…”
Section: Characterization and Activity Of Subabmentioning
confidence: 99%